Recent advances in understanding the role of uterine microbiota in endometrial receptivity and its impact on embryo implantation failure: Uterine microbiota and embryo implant failure - Li, Yuhong; Li, Qiuping; Chen, Dandan; Mao, Wei; Zhang, Yun (Cellular and Molecular Biology, 2024)
The aim was to provide a review of studies on the impact of intrauterine bacterial flora on endometrial tolerance in populations with failed embryo implantation and to provide direction for future clinical practice. Studies utilizing techniques such as 16S rRNA gene sequencing and macrogenomics were included through a comprehensive literature search to identify studies examining the correlation between intrauterine bacteria and endometrial tolerance. The composition of the bacterial flora in the uterine cavity plays an important role in regulating endometrial tolerance, and an increase in specific dominant bacilli in the uterine cavity correlates with an increase in conception rates, whereas dysbiosis of the intrauterine flora may lead to a variety of reproductive complications, including intrauterine inflammation, uterine adhesions, endometriosis, failure of embryo implantation, recurrent miscarriages, and embryo developmental arrest. Understanding the impact of intrauterine bacteria on endometrial tolerance can help improve clinical outcomes in patients experiencing embryo implantation failure. Further research in this area will help to elucidate the underlying mechanisms and develop targeted therapeutic interventions to optimize endometrial affinity and improve reproductive outcomes.